Early Activation of the Kaposi's Sarcoma-Associated Herpesvirus RTA, RAP, and MTA Promoters by the Tetradecanoyl Phorbol Acetate-Induced AP1 Pathway - Wang, Shizhen Emily (American Society for Microbiology, 2004)
Kaposi's sarcoma-associated herpesvirus (KSHV) maintains a latent infection in primary effusion lymphoma (PEL) cells, but treatment with tetradecanoyl phorbol acetate (TPA) can trigger the full lytic-cycle replication in some of these cells. During lytic-cycle replication, the KSHV-encoded replication and transcription activator (RTA or ORF50), the mRNA transport and accumulation protein (MTA), and the replication-associated protein (RAP) all play crucial roles in expression of downstream viral genes as well as in mediation of viral DNA replication. The cellular CCAAT/enhancer-binding protein alpha (C/EBPα) is induced in TPA-treated PEL cells and contributes to transactivation of the promoters for all of these genes through both direct binding and cooperative interactions with RTA and RAP targeted to upstream C/EBP sites. However, little is known about how RTA expression is triggered initially at the earliest stages after TPA induction when the C/EBPα levels are still limited. Treatment with TPA proved to significantly induce both AP1 DNA-binding activity and levels of activated phosphorylated cJUN in PEL cells and ectopic expression of cJUN-plus-cFOS-induced RTA protein expression in PEL cells. Cotransfected cJUN plus cFOS or TPA treatment transactivated the KSHV RTA, RAP, and MTA promoters in an AP1-binding site-dependent manner in all three promoters. Chromatin immunoprecipitation assays confirmed that cJUN associates with these KSHV target promoters in PEL cells as early as 4 h after TPA treatment. Furthermore, the KSHV RTA and RAP proteins both interact with cJUN or both cJUN and cFOS in vitro or by coimmunoprecipitation from induced PEL cells and enhance cJUN-plus-cFOS-mediated transactivation of these viral promoters. Both increased phosphorylated cJUN and AP1 DNA-binding activity was detected as early as 1 h after TPA treatment in PEL cells, suggesting that AP1 activity may be crucial for very early activation of the RAP, MTA, and RTA promoters during the KSHV lytic cycle. Finally, expression of RTA alone increased cJUN protein levels severalfold in DG75 cells but did not induce cJUN phosphorylation. Therefore, we suggest that the initiating effects of TPA via the AP1 pathway in PEL cells need to be amplified by RTA for full lytic-cycle induction.